Elucidating Sequence and Structural Variations Present in RNase P RNA Ribozyme for the Taxonomy of Leptospira spp. - Ravishankar, Vigneshwaran; Karunanidhi, Manasha; Sridhar, Nivetha; Lourdu, Stephen Raj Michael Dason (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
RNase P RNA (RPR) gene responsible for transcribing tRNA processing ribozyme is an essential single-copy gene present in the genome of all organisms and has been proven to be a reliable genetic marker for the differentiation of species. In the present study, phylogenetic analysis was performed by exploiting sequence and structural variations present in the RPRs to determine the taxa of unidentified leptospires. RPR gene-based phylogeny revealed that serovars of Leptospira borgpetersenii could be bifurcated into distinct subgroups A and B. The saprophytic leptospiral strains were classified into three groups namely saprophytic group I, saprophytic group II and saprophytic group III. The presumed taxonomic positions of leptospiral strains Hampton, LT 2116, M4, 18R, Pond 2020, ZV016, ICFT and L. alexanderi were investigated for the phylogeny using both RPR and secY genes. The strains of L. alexanderi branched out as a separate clade between strains of L. santarosai and L. borgpetersenii. Furthermore, a simple restriction digestion assay was performed for the RPR gene-based differentiation of leptospires. PCR amplification and subsequent restriction digestion of the RPR gene amplified helped to distinguish Leptospira sp. The present research contributes to our understanding of leptospiral taxonomy and provides a valuable tool for species identification in diagnostic applications.